Fabrication and application of three-dimensional nanocomposites modified electrodes for evaluating the aging process of Huangjiu (Chinese rice wine). (15th March 2022) - Wei, Zhenbo; Zhang, Jinyang; Shao, Wenqing; Wang, Jun
Highlights: Three types of TDCPNs modified electrodes were fabricated to evaluate aging process. Chronoamperometric methods were used to obtain the aging information from rice wines. VIF was used to optimize the features by removing multicollinearity information. PCA, LLE and LPP with optimized features were applied for classifying wine samples. LLE-ELM was proved the best method for evaluating the aging processes of rice wines. Abstract: In this study, three modified glassy carbon electrodes based on three-dimensional conducting polymer nanocomposites (TDCPNs) were fabricated for evaluating the aging process of Huangjiu (Chinese rice wines). The electrochemical activity and experimental conditions of the TDCPNs modified electrodes were investigated by cyclic voltammetry, the aging information obtained by the modified electrodes were optimized by variance inflation factor (VIF). Principal components analysis (PCA), locally linear embedding (LLE), and locality preserving projection (LPP, which presented the best classification result) based on the optimized data were applied to classify the wine samples. Then, the dimensionality reduction data of PCA, LLE, and LPP were used as input variables of the logistic regression and extreme learning machine (ELM) for evaluating the aging process of Huangjiu, and the LLE-ELM method exhibited the best prediction results. These results demonstrated that the TDCPNs modified electrodes presented the potential for the quality analysis of food and beverages.